Two independent alleles at 6q23 associated with risk of rheumatoid arthritis - Plenge, Robert M; Cotsapas, Chris; Davies, Leela; Price, Alkes L; de Bakker, Paul I W; Maller, Julian; Pe'er, Itsik; Burtt, Noel P; Blumenstiel, Brendan; DeFelice, Matt; Parkin, Melissa; Barry, Rachel; et al. (Nature genetics, 2007)
This is an issue edsumm for 27. Identification of the Palaeocene/Eocene thermal maximum in a marine sedimentary sequence. To identify susceptibility alleles associated with rheumatoid arthritis, we genotyped 397 individuals with rheumatoid arthritis for 116,204 SNPs and carried out an association analysis in comparison to publicly available genotype data for 1,211 related individuals from the Framingham Heart Study 1 . After evaluating and adjusting for technical and population biases, we identified a SNP at 6q23 (rs10499194, ∼150 kb from TNFAIP3 and OLIG3 ) that was reproducibly associated with rheumatoid arthritis both in the genome-wide association (GWA) scan and in 5,541 additional case-control samples ( P = 10 −3 , GWA scan; P < 10 −6 , replication; P = 10 −9 , combined). In a concurrent study, the Wellcome Trust Case Control Consortium (WTCCC) has reported strong association of rheumatoid arthritis susceptibility to a different SNP located 3.8 kb from rs10499194 (rs6920220; P = 5 × 10 −6 in WTCCC) 2 . We show that these two SNP associations are statistically independent, are each reproducible in the comparison of our data and WTCCC data, and define risk and protective haplotypes for rheumatoid arthritis at 6q23.